Morphological alterations of the bone marrow in patients with COVID-19. Systematic review and meta-analysis - Pichardo-Rodriguez, Rafael (2022)
Introduction: Despite the fact that hematological alterations at the peripheral level are widely known, little is known about the alterations caused by COVID-19 at the bone marrow level. Objective: To determine the morphological alterations of the bone marrow caused by COVID-19. Material and methods: Systematic review and meta-analysis. Observational studies and reports and case series were included and editorials, reviews, letters to the editor were excluded. A search was performed in Pubmed, ScienceDirect and Scielo. The risk of bias was assessed using the NewCatell-Ottawa and Hassan Murad scales for case reports and series. The outcomes were the morphological parameters of the bone marrow. For the quantitative synthesis of the information, a proportion meta-analysis was performed using random effects in RStudio. Results: Hypercellularity occurred in 65% (95% CI: 51%-78%), maturation arrest of the myeloid series occurred in 57% (95% CI: 29%-83%). and the alteration of the M/E ratio occurred in 60% (95% CI: 46%-74%). Conclusion: The most frequent morphological alterations in the bone marrow were hypercellularity, arrest in myeloid maturation and alteration of the M/E ratio in patients with COVID-19.